Empreendedorismo internacional na captação de recursos internacionais das organizações do terceiro setor - Lorca, Mariana Cristina Betti Cury (2016)
Research has shown that International Entrepreneurship (EI) and International Entrepreneurial Orientation (OEI) are present in behaviors that lead to the internationalization of companies. Private organizations, not-for-profit, belonging to the third sector of the society, have played an important role in the international development agenda, contributing directly or indirectly to the implementation of environmental and humanitarian actions, reduction of poverty and the defense of rights and social equality. Nevertheless, research on EI and OEI in this type of organization are still incipient. Additionally there is a lack of research to understand the Entrepreneurship in Emerging Economies. This research contributes to overcoming this gaps by analyzing whether and how three central constructs of EI and OEI - proactiveness, innovativeness and risk-taking - are related to fundraising by these organizations. Through a multiple cases study it was found, at an exploratory level, that these constructs are related to fundraising and that they explain performance differences among organization with respect to this goal. The research contributes to the theory of EI and OEI by expanding the field in which the validity of core constructs of these theoretical perspectives have been checked. It contributes to the management of these organizations by indicating what entrepreneurial behaviors can increase fundraising .